Quality of life at work: scope of health promotion interventions in a hospital environment (Research, Society and Development, 2020)
The objective of the study was to evaluate the scope of health promotion interventions adopted in a hospital. This is a cross-sectional survey conducted with 13 hospital managers. The CDC - Worksite Health Score Card (HSC) questionnaire was used. The data were analyzed using descriptive statistics. Comparing the scores of the 12 sections of the HSC individually, it was observed that eight had scores and four did not score. Starting to verify the questions that obtained the answer “yes” and their score, where 1 is good, 2 is very good and 3 is great, it is clear that the studied institution has health promotion activities aimed at workers. Of the 26 questions that have an impact level of 1, the institution answered yes in eight, equivalent to 31% of strategies with a good impact on health. Of the 30 questions with impact value 2, the institution answered yes in four, equivalent to 13% of actions with a very good impact on health. Finally, of the 43 impact level 3 questions, the institution answered yes in eight, the equivalent of 19% of activities with an optimum level of impact. The institution studied, although not organized in programs, develops health promotion practices in the hospital work environment with good, very good and excellent impact levels.